The Persistence of Regional New Business Formation-Activity over Time - Assessing the Potential of Policy Promotion Programs - Michael Fritsch; Pamela Mueller (Max Planck Institute for Research into Economic Systems, 2005)
We investigate regional differences in the level and the development of regional new business formation activity. There is a pronounced variance of start-up rates across the regions. The level of regional new firm formation is rather path-dependent so that changes are relatively small. The main factors determining the level of regional start-ups are innovation and entrepreneurship. These factors also seem to be responsible for changes in the level of regional new business formation. In addition, unemployment plays a role. Steering innovation and creating an entrepreneurial atmosphere could be an appropriate starting point for policy measures that try to promote start-ups. Our empirical evidence strongly suggests that such measures may have significant effect only in the long run.
Keywords: O1; R11; M13; O18; 330; New businesses; entrepreneurship; growth regimes; time lags; Unternehmensgründung; Region; Zeit; Wirtschaftsförderung; Lag-Modell; Innovationspolitik; Unternehmer; Deutschland